Synthesis of a 3-Thiomannoside - Comba, María Betina (2016)
An efficient and straightforward synthesis of a novel 3-thiomannoside derivative (1,2,4,6-tetra-O-acetyl-3-S-acetyl-3-thio-β-d-mannopyranoside) was developed starting from levoglucosenone. A xanthate-thiocarbonate exchange under acidic conditions was the key step for the new C-S bond. The product was obtained enantiospecifically in very good overall yield.